C1q and HBHA-specific IL-13 levels as surrogate plasma biomarkers for monitoring tuberculosis treatment efficacy: a cross-sectional cohort study in Paraguay - Russomando, Graciela; Sanabria, Diana; Díaz Acosta, Chyntia Carolina; Rojas, Leticia; Franco, Laura; Arenas, Rossana; Delogu, Giovanni; Ndiaye, Mame Diarra Bousso; Bayaa, Rim; Rakotosamimanana, Niaina; Goletti, Delia; Hoffmann, Jonathan (Frontiers in Immunology, 2024)
New diagnostic tools are needed to rapidly assess the efficacy of pulmonary tuberculosis (PTB) treatment. Aim of this study was to evaluate several immune biomarkers in an observational and cross-sectional cohort study conducted in Paraguay. Thirty-two patients with clinically and microbiologically confirmed PTB were evaluated before starting treatment (T0), after 2 months of treatment (T1) and at the end of treatment (T2). At each timepoint plasma levels of IFN-y, 17 proand anti-inflammatory cytokines/chemokines and complement factors C1q, C3 and C4 were assessed in unstimulated and Mtb-specific stimulated whole blood samples using QuantiFERON-TB gold plus and recombinant Mycobacterium smegmatis heparin binding hemagglutinin (rmsHBHA) as stimulation antigen. Complete blood counts and liver enzyme assays were also evaluated and correlated with biomarker levels in plasma. In unstimulated plasma, C1q (P<0.001), C4 (P<0.001), hemoglobin (P<0.001), lymphocyte proportion (P<0.001) and absolute white blood cell count (P=0.01) were significantly higher in PTB patients at baseline than in cured patients. C1q and C4 levels were found to be related to Mycobacterium tuberculosis load in sputum. Finally, a combinatorial analysis identified a plasma host signature comprising C1q and IL-13 levels in response to rmsHBHA differentiating PTB patients from cured TB profiles, with an AUC of 0.92 (sensitivity 94% and specificity 79%). This observational study provides new insights on host immune responses throughout anti-TB treatment and emphasizes the role of host C1q and IL-13specific response as surrogate plasma biomarkers for monitoring TB treatment efficacy.